Analysis Of The Legal Status Of Forced Marriage (IJBAR) By Wali Mujbir In Marriage From The Perspective Of Islamic Law - M. Thahir*; Ismail Nasution (Riwayat: Educational Journal of History and Humanities, 2023)
This paper examines the concept of hak ijbar, which refers to the right of a guardian to marry off his daughter without her consent. There are differing views on this concept between the madhhab imams and the Indonesian Marriage Law, due to different interpretations of the Prophetic hadith. The right of ijbar should be seen as a form of protection or responsibility of the father, given the assumption that his daughter may not have the capacity to make her own marriage decision. This article raises several issues, including the causes of forced marriage by the mujbir guardian, scholars' views on forced marriage (ijbar), and its legal status from the perspective of Islamic law. Using the literature research method and various theories, the research shows that forced marriages often occur due to parents' desire to bring them closer together. However, forcing a girl to marry a man she does not love is a form of injustice. According to the Shafi'i Madhhab, the mujbir guardian has the right to force his virgin daughter to marry, but this right does not apply to a woman who is not a virgin without her consent.